Pragmatic of Deictics in the Narratives of the Reasons for the Revelation of the Qur’an - سطوف عزوز; كاتب حسن (Milev Journal of Research and Studies, 2023)
Pragmatics expanded the horizons of linguistic and literary research alike due to the breadth of its fields and the multiplicity and richness of its procedures, as well as its attention to the critical conditions of creating and interpreting discourse. Among these deliberative fields, we chose, aiming deictics to monitor them from the Holy Qur’an, so we show their references and contexts from the narratives of the reasons for the revelation of the Qur’an, all with a deliberative approach. Therefore, the research aims to answer the following problems: What is pragmatic? What are deictics signs and what are their types? What are the reasons for the revelation of the Qur’an? How do the narratives of the reasons for the revelation of the Qur’an contribute to clarifying the references and referrals of the deictics, their interpretation, and the determination of their purposes? We have come to a basic conclusion that the verse or verses, together with the reason for its revelation, constitute a single context, and from it the reference to the deictics is known, so the ambiguity and ambiguity disappears, and the intent becomes clear. Because the deictics are vague.